Genetic and phylogenetic characterization in the genus Paspalum using molecular marquers - Pereira, J.; Fajardo, A.; Sabbía, V. (Agrociencia Uruguay, 1999)
Paspalum is an important genus of the family Grarnineae which includes several valuable forage grasses. Many of the species are polyploid and no important levels of variability have been found in naturally ocurring populations. In orther to investigate the diversity, ploidy, phylogenetic relationships and characterize new hybrids, 24 decameric primers were aplied for random amplification of polymorphic DNA (RAPD). Sixteen primers were found to be suitable to produce discrete profiles and distinguished among, di, tetra, penta and hexaploid materials. Leaf tissue of individual plants was used as the source of DNA so that the taxonomic value of each species was conserved. RAPD profiles, with the plants tested, distinguished among species di, tetra, penta and hexaploids. Sexual clones and interspecific hybrids were distinguished from progenitors. All the results were consistent in the genetic distances, phylogenetic, and multivariate analysis. At the intraspecific level, P. dilatatum ssp.flavescens, showed genetic variability among accessions which is in agreement with phenotypic characters. Toe methodology described and the results presented in this study can be applied to the caracterization of P. dilatatum populations, to identify hybrid progenies in Paspalum breeding programs and to explore further phylogenetic relationships within this genus.